SOCIO-CULTURAL ASPECT OF INTER-ETHNIC TOLERANCE OF YOUTH IN THE POLYCULTURAL ENVIRONMENT OF KAZAKHSTAN AND BELARUS - Ussenova, Aida; Malakhova, Irina; Mailybaeva, Gulmira; Assylova, Raushan; Zhabykbayeva, Dinara; Tynyskhanova, Aiym (PEOPLE: International Journal of Social Sciences, 2019)
The article deals with the study of the problem of interethnic tolerance, the activity of ethnocultural associations aimed at forming interethnic tolerance of youth in a multicultural environment. As forms of socio-cultural activities of youth in the conditions of the Republic of Belarus is analyzed the theoretical and methodological approaches to the problem of interethnic tolerance in foreign practice, patterns, and principles of the functioning of ethnocultural associations. Also on the example of the Republic of Kazakhstan is analyzed mechanisms of educational influence of the multicultural environment on the process of forming interethnic tolerance of youth. Particular attention is drawn to the study of new educational strategies and approaches to the formation of interethnic tolerance of youth in the sphere of culture, where the specifics of the Kazakhstan-Belarusian experience of organizing this socially significant segment of educational services can be useful to other countries. For achieving the goal of the work were used the materials of scientific publications and applied research of the authors of the article in the field of pedagogy. On the basis of the conducted research is proposed scientifically grounded conclusions and recommendations on organizing the process of formation of interethnic tolerance of youth in a multicultural environment. The results of the research can be used in the system of retraining and advanced training of personnel in the sphere of culture and education, and can also be a guide for the cultural policy of state organizations in educational programs for organizing leisure time for young people at the international level.